THU0141 Painless Synovitis – A Silent Enemy? A Controlled, Ultrasound, Radiographic, Clinical Trial. (23rd January 2014) - Pereira, D. F.; Natour, J.; Buosi, A. L.; Ferreira, F.; Fernandes, A.; Furtado, R. N.; ,
Abstract : Background: Some rheumatoid arthritis (RA) patients exhibit persistent chronic synovitis marked by joint swelling that may or may not be accompanied by pain. Objectives: The aim of the present study was to compare painless and painful chronic synovitis in established RA with regard to clinical, ultrasonography (US), radiography and laboratory outcomes. Methods: A cross-sectional study was carried out involving 60 patients with RA and synovitis in the metacarpophalangeal joints (MCPs): 30 patients without pain and 30 patients with pain for at least 6 months. The radiocarpal, distal radioulnar joints and MCPs were evaluated using US gray scale (US-GS), power Doppler (US-PD) and radiography. Past and present clinical and laboratory findings were also evaluated. Results: No statistically differences between groups were found for the most of outcomes analyzed. Worse scores on the disease activity indices (DAS 28 and SDAI) (p<0.001), questionnaires of function (HAQ and Cochin) and pinch strength (p < 0.001 to 0.039) were found in the group with pain. The logistic regression analysis revealed that the use of an immunobiological agent was associated with a threefold greater chance of belonging to the group with pain (p = 0.049). No statistically significant differences were found for the majority of variables analyzed by radiography and US (including PD assessment). However, worse joint damage scores (erosion and cartilage) were found in the group without pain. Conclusions: Patients with RA and painless chronic synovitis exhibited similar disease progression, radiographic and US findings to those with painful chronic synovitis. Although similar between groups, the US evaluation demonstrated worse joint damage scores in patients with painless synovitis. References: Bugatti S, Manzo A, Caporati R et al. Assessment of synovitis to predict bone erosions in rheumatoid arthritis. Ther Adv Musculoskeletal Dis 2012; 4(4):235-244. Naredo E, Bonilla G, Gamero F et al. Assessment of inflamatory activity in rheumatoid arthritis: a comparative study of clinical evaluation with gray scale e power Doppler ultrasonography. Ann Rheum Dis 2005;64:375-381. Brown AK, Quinn MA, Karim Z, Conaghan PG, Peterfy CG, Hensor E, Wakefield RJ, O'Connor PJ, Emery P. Presence of significant synovitis in rheumatoid arthritis patients with disease-modifying antirheumatic drug-induced clinical remission – Evidence from an imaging study may explain structural progression. Arthritis Rheum. 2006;54(12):3761-3773. Filippucci E, da Luz KR, Di Geso L, et al. Interobserver reliability of ultrasonography in the assessment of cartilage damage in rheumatoid arthritis. Ann Rheum Dis 2010; 69(10):1845-8. Disclosure of Interest: None Declared